2011
DOI: 10.1016/j.ygeno.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Differential global gene expression in cystic fibrosis nasal and bronchial epithelium

Abstract: Respiratory epithelium is the target of therapies, such as gene therapy, for cystic fibrosis (CF) lung disease. To determine the usefulness of the nasal epithelium as a pre-screen for lung-directed therapies, we profiled gene expression in CF and non-CF nasal and bronchial epithelium samples using Illumina HumanRef-8 Expression BeadChips. 863 genes were differentially expressed between CF and non-CF bronchial epithelium but only 15 were differentially expressed between CF and non-CF nasal epithelium (≥1.5-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 40 publications
6
73
2
Order By: Relevance
“…These results are concordant with the known inflammatory nature of the CF lung and show a similar profile to that found by others (Ogilvie et al, 2011). For example, target of Myb1 (TOM1) is a negative regulator of TLR2/4 signalling, that is significantly up-regulated in CF bronchial epithelial cells (Oglesby et al, 2010); TOM1 mRNA expression was also increased in the CF samples tested in this study (data not shown).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are concordant with the known inflammatory nature of the CF lung and show a similar profile to that found by others (Ogilvie et al, 2011). For example, target of Myb1 (TOM1) is a negative regulator of TLR2/4 signalling, that is significantly up-regulated in CF bronchial epithelial cells (Oglesby et al, 2010); TOM1 mRNA expression was also increased in the CF samples tested in this study (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have profiled mRNA expression within the context of CF. At least three studies have profiled mRNA expression in the CF nasal epithelium (Ogilvie et al, 2011, Wright et al, 2006, Clarke et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the nine genes in class VII ( Figure 3B), i.e., whose siRNA no longer inhibit ENaC under aprotinin nor under Nedd4-2-siRNA, could be related to such crosstalk: KCNQ3, TAS2R1, TNFRSF1B, B4GALT6, KIFAP3, CDK10, GRINA, SCGB3A1, and IFIH1 (Dataset S4). One of these (SCGB3A1) is downregulated in CF nasal epithelium (Clarke et al, 2013) and CF bronchial epithelium (Ogilvie et al, 2011) and upregulated during air-liquid interface differentiation of human bronchial epithelial cells (Ross et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Besides our own nasal epithelial cell study (Clarke et al 2013), we chose 2 other CF data sets, one measuring gene expression in bronchial epithelial brushings (Ogilvie et al 2011), and one in foetal tracheal cell lines (Verhaeghe et al 2007). We added other studies measuring gene expression in chronic lung diseases, namely chronic obstructive pulmonary disorder (COPD: Bhattacharya et al 2009), idiopathic pulmonary fibrosis (IPF: Meltzer et al 2011) and asthma (Kicic et al 2010),…”
Section: Datamentioning
confidence: 99%